Analisis Kadar Zat Organik pada Air Sumur Warga Sekitar TPA dengan Metode Titrasi Permanganometri - Apriyanti, Apriyanti; Apriyani, Ersy Monica (ALKIMIA, 2018)
Groundwater is one of the main alternatives for people to get clean water easily, because the construction is relatively easy. Therefore residents around the landfill use ground water. Final Disposal Site (TPA) is a place where waste has reached the final stage in its management. Well water around the landfill will usually be polluted by various chemicals that are harmful to the body, one of which is organic matter. Organic substances are substances that contain a lot of carbon. Examples are benzene, chloroform, detergent, and pentachlorophenol. High levels of organic matter indicate that the water has been polluted. Therefore, the determination of the level of organic matter in the samples of borehole water so that the quality can be known quality. To determine the level of organic matter in the sample of community drill well water, quantitative analysis was carried out using the permanganometric titration method. The principle of the permanganometric titration method is that organic matter can be oxidized with KMnO4 in an acidic atmosphere by heating. The remaining KMnO4 is reduced with excess oxalic acid. The excess oxalic acid is titrated again with KMnO4. Based on the results of the analysis, the levels of organic matter contained in well water samples amounted to 586.8 mg / L. So it can be concluded that the sample of community drill well water is not suitable for drinking, because it does not meet the criteria of drinking water. The criteria for drinking water according to the Minister of Health of the Republic of Indonesia No.492 / MENKES / SK / VI / 2010 are not containing more than 10 mg / L of organic matter. This is because the amount of organic matter will result in increasing the population of microorganisms and can lead to the development of dangerous pathogenic bacteria in the human body, especially for the immune system.